Collocability in Languages for Special Purposes (LSPs): Some Preliminaries - Knowles, Francis E. (Lexikos, 1997)
This paper is concerned with the language professional discourse communities use for their internal communication. The characteristics of these languages for special purposes (LSPs) are many and varied, as well as being underresearched. The focus adopted here is to examine the phenomenon of multiword units, many of which are orthographic pluralities designating conceptual singularities. It is important to recognise at the outset that colocation is not the same as collocation. Analysis and systematisation of these textual "clusterings" is intended to separate them into two radically different types of entity: multiword segments possessing terminological status; and collocative material. The methods used to achieve the above objective are both qualitative, i.e. micro-environmental analysis, and quantitative, i.e. statistical patterning exhibiting a certain level of frequency and constancy. Collocational material quoted here also shows by its configuration that discourse communities use collocations to which the general public are not inured and with which they may not necessarily be familiar at all. Keywords: chunking; co-occurrence; cognitive entity; collocability; concept; corpora; discourse community; distribution; dyad; encyclopaedic competence; language for special purposes; lexicography; mental lexicon; multiword unit; occurrence; sociolect; statistics; terminology; term; triad